Frequency of Target Language Use by Learners in a Foreign Language Education Context - Jannah, Raudlotul; Milal, A. Dzo’ul (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
Target language use (TLU) has traditionally been analyzed as an independent variable impacting language proficiency. However, there is a significant research gap regarding the pre-existing contextual factors that determine TLU frequency as a dependent variable. This descriptive study examines the extent of TLU and its underlying drivers among students and faculty members at a State Islamic University of Sunan Ampel Surabaya. Utilizing a mixed-method approach- comprising questionnaires, interviews, and observations-the research categorizes TLU into pedagogical (self-motivated study) and authentic (communicative) purposes. The study reveals that the learners’ target language use is for pedagogic (self-motivated study) and authentic (communicative) purposes. Students tended to use the target language pedagogically more than authentically. The contextual variables comprise students’ internal and external factors, including affective aspects, in-and-out-class activities, and social and situational language environments. The classroom teaching-learning strategies conducted by the lecturers mostly facilitated the pedagogical use. Since the success of foreign language learning is determined, among others, by the frequency of target language use, its influential factors need to be managed well so that the target language use is promoted and maximized.